The Urgency of Understanding the Definition and Category of Teaching Materials as Knowledge for Biology Education Students - Wahyuni, Sri; Rahmawati, Sri; Sudibya, Eka; Lestari, Juniarti Wulan; W. D.Therik , Johannis; M Pekei, Imelda F.I (International Journal of Sustainable English Language, Education, and Science, 2024)
This research discusses the development of teaching materials needed in the world of education. This research uses a skinative research method with secondary data methods, namely through literature studies. Teaching materials are one of the most important components in the learning process, and can help students learn more easily. Instruction consists of two categories: printed instructions and non-printed instructions. One type of printed teaching material is textbooks. Teaching materials can be defined as any type of material used to help teachers or instructors carry out teaching and learning activities in the classroom. Print teaching materials through the media of books, handouts, maps, magazines, etc. Non-print teaching materials audio programs, display teaching materials, overhead transparencies (OHT) models, videos and computer-assisted teaching materials. Knowledge of teaching materials is needed so that students can apply it in the form of product development or research related to teaching materials. In learning biology, delivery requires teaching material media as a lat in channeling knowledge.